2018
DOI: 10.1097/mao.0000000000002032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vestibulo-ocular Reflex Gain and Catch-up Saccades During Vestibular Rehabilitation

Abstract: Objective: To assess, in patients referred to vestibular rehabilitation (VR) for persistence of disability after acute unilateral vestibulopathy (AUV), whether the video head impulse test (vHIT) can be a useful technique to define the efficacy of the treatment. Study Design: Prospective clinical study. Setting: Tertiary academic referral hospitals. Patients: Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 24 publications
2
31
0
2
Order By: Relevance
“…As reported by numerous previous investigators [5,7,22,23,25,[57][58][59][60][61], we found that as the VOR loss increased compensatory saccade characteristics generally followed a similar pattern: the amplitude, frequency, and clustering increased while the latency became earlier (Fig 8). The rate of these changes to the reduction in VOR gain depended on both the visual condition and saccade number.…”
Section: Discussionsupporting
confidence: 87%
“…As reported by numerous previous investigators [5,7,22,23,25,[57][58][59][60][61], we found that as the VOR loss increased compensatory saccade characteristics generally followed a similar pattern: the amplitude, frequency, and clustering increased while the latency became earlier (Fig 8). The rate of these changes to the reduction in VOR gain depended on both the visual condition and saccade number.…”
Section: Discussionsupporting
confidence: 87%
“…Although this was not determined to be statistically significant, it has been objectively reflected in a previous study which showed that the ''PR'' index (representing the scattering pattern) reduced in patients with acute unilateral vestibulopathy after VR. 13 In the long-term results of the current study of patients with vestibular deafferentation, the percentages of the organized pattern were found to be very high.…”
Section: Discussionmentioning
confidence: 49%
“…Despite a lack of objective data, this can be considered to be related to the mobility or sedentary lifestyle of the patient, and the decrease in the number of overt saccades in patients undergoing VR supports this idea. 13 Based on this, a patient with scattered saccades and complaints of dizziness may be a true candidate for VR. Therefore, VHIT can be recommended as a valuable tool for postoperative follow-up of vestibular differentiation patients to be able to select suitable VR candidates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations